PRONUNCIATION ERRORS MADE BY SENIOR HIGH SCHOOL STUDENTS IN READING ENGLISH TEXTS ALOUD (Universitas Negeri Semarang, 2014)
The objective of this study was to identify the types of pronunciation error, causes of pronunciation error, the teacher/students way to overcome pronunciation error, and teacher’s influence in causing students pronunciation error. The method of this study was descriptive qualitative. The objects of this study were 15 students of eleventh graders Global Madani School Bandar Lampung. The texts were 15 texts consisted of 2.417 words. The text were read by the students then were analyzed by the researcher. The result of the data analysis showed that the student’s pronunciation errors were defined into three types. They were pre-systematic, systematic, and post-systematic errors. The students got the difficulties in pronouncing /ŋ/, /d/, /ʤ/, /ʧ/, /z/, /ð/, /θ/, /∫/, and /g/. These phoneme errors were found in the initial, medial and final positions of the words. The causes of errors were interference, intralingual and developmental errors. Interference errors were dialect, accent and the similarities of pronouncing the words between L1 and L2. Intralingual error was the result of the student’s generalization. The developmental error was the student’s result of lack of interlanguage knowledge. The teacher overcomes the errors by three ways. They were repetition, silence and correction.